Assessment of the effectiveness of physiotherapy in the treatment of shoulder pain syndrome - Alicja Mirus; Krzysztof Zdziarski (Kazimierz Wielki University, 2022)
Abstract Painful shoulder syndrome is a common condition of the musculoskeletal system in adults.  This disorder affects your ability to work, overall body function, sleep, and quality of life.  The treatment of shoulder syndrome is multifaceted and covers a broad spectrum of physiotherapy options. These include progressive strengthening exercises, laser therapy, electrotherapy and magnetotherapy. There are a number of treatments available that are reimbursed by the National Health Fund (NFZ). Aim of the research: The aim of the research was to assess the impact of rehabilitation on the treatment of shoulder pain syndrome. Material and methods: The method used in the study was a diagnostic survey. The research was supplemented with an author's questionnaire to compare demographic data and assess the quality of life.  The ranges of mobility were assessed before and after 10 series of treatments and the level of pain using the VAS scale.  The study involved 80 patients presenting with the diagnosis of painful shoulder syndrome, 60% of whom were women and 40% men. The most numerous age group was between 50-60 years old (31 people) and 30-40 years old (24 people).  Results: The treatment process was successful in patients.  Out of the studied population, 95% of patients experienced an improvement in their health compared to the baseline.  A significant reduction in pain was observed with the use of physiotherapeutic procedures.  The patients most favorably assessed massage, kinesiotherapy and cryotherapy. Conclusions: Conservative treatment reimbursed under the National Health Fund is an effective method of improving mobility and reducing to a large extent discomfort in the shoulder joint.